Vehicles of Meaning: Unconventional Semantics and Unbearable Interpretations - Laurence R. Horn (Washington University Law Quarterly, 1995)
I try my hand at the noble pursuit of ambulance chasing. The question is whether the city ordinance in “All vehicles are prohibited from Lincoln Park.” will be construed so as to exempt ambulances and, if so, whether they are exempted by virtue of the function of all or vehicle as 'regulatory variables' in the interpretation of the ordinance.
Keywords: Linguistics